1999
DOI: 10.1093/ije/28.2.281
|View full text |Cite
|
Sign up to set email alerts
|

Variation in physical fitness between ethnic groups in nine year olds

Abstract: Shorter and obese children have poorer physical fitness than other children. Physical fitness is lower in children originating in the Indian subcontinent than other British children. This seems to be unrelated to socioeconomic disadvantage. Physical inactivity and lack of cycling skills may explain our findings.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
10
0
2

Year Published

2004
2004
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 18 publications
(14 citation statements)
references
References 25 publications
2
10
0
2
Order By: Relevance
“…It has also been reported that overweight as well as obese children showed a lower physical fitness than normal children. 19,[26][27][28] In one study, the negative relationship between physical fitness and WC has also been documented. 19 The results of the present study are concordant with these observations since physical fitness was significantly associated with BMI of boys and girls in grades 2 and 4.…”
Section: Discussionmentioning
confidence: 99%
“…It has also been reported that overweight as well as obese children showed a lower physical fitness than normal children. 19,[26][27][28] In one study, the negative relationship between physical fitness and WC has also been documented. 19 The results of the present study are concordant with these observations since physical fitness was significantly associated with BMI of boys and girls in grades 2 and 4.…”
Section: Discussionmentioning
confidence: 99%
“…However, South Asians living in the UK have consistently been shown to have lower levels of physical activity than the general population [8], [9], a trend which begins in early life [10], [11], and is likely to be an important contributor to this increased incidence and poor health outcomes. Recent UK research has shown that deaths from coronary heart disease are substantially more common in people from South Asian backgrounds than those of White origins,(hazard ratio: 2.87, 95%CI 1.74 to 4.73) with this increased risk being particularly evident in Bangladeshi- and Pakistani-origin populations [12].…”
Section: Introductionmentioning
confidence: 99%
“…The 2004 Health Survey for England data reported lower levels of physical activity in South Asian groups compared with the general UK population and other ethnic minority groups (77), and other studies showed similar results in migrant and urban South Asians (6,15,82,83,84,85,86,87). This low level of physical activity is already present in children and adolescents (77,85,88,89,90,91).…”
Section: Diet and Exercisementioning
confidence: 87%